Co-phylogeographic study of the flatworm Gyrodactylus gondae and its goby host Pomatoschistus minutus. Issue 2 (April 2017) - Huyse, Tine; Oeyen, Merel; Larmuseau, Maarten H.D.; Volckaert, Filip A.M.
Abstract: We performed a comparative phylogeographic study on the monogenean flatworm Gyrodactylus gondae Huyse, Malmberg & Volckaert 2005 (Gyrodactylidae) and its sand goby host Pomatoschistus minutus (Pallas, 1770) (Gobiidae). G . gondae is a host-specific parasite with a direct life cycle and a very short generation time. These properties are expected to increase the chance to track the genealogical history of the host with genetic data of the parasite ('magnifying glass principle'). To investigate this hypothesis we screened nine sand goby populations ( n = 326) along the Atlantic coasts of Europe for Gyrodactylus specimens. Low parasite prevalence resulted in partially overlapping host and parasite datasets. Ninety-two G . gondae collected on five sand goby populations were subsequently sequenced for a 460 bp cytochrome c oxidase subunit II ( coxII ) fragment, which, in combination with previously published haplotype data for the hosts, allowed for partially overlapping host and parasite datasets. Haplotype diversity was lowest in the Irish Sea while nucleotide diversity was highest in the Southern North Sea. The host population also showed the lowest diversity in the Irish Sea but the highest nucleotide diversity, based on cytochrome b sequences of 850 bp, was found in Skagerrak. Phylogeographic networks suggest postglacial expansion in both the host and the parasite. Pair-wise population differentiation was however not consistently higher in the parasite than in the host, rejecting the magnifying glass hypothesis for this host-parasite system. The parasite network offered limited resolution and was characterized by many extinctions and/or missing haplotypes, which could be attributed to 1) sampling bias, 2) size fluctuations in the parasite populations resulting in frequent extinctions and genetic drift and 3) the relatively young age of the host-parasite association. A more exhaustive study including a broader geographical and genomic coverage is needed to discriminate among these competing hypotheses. Graphical abstract: Highlights: Both host and parasite phylogeographic networks show postglacial expansion. Similar host and parasite phylogeographic networks suggest co-evolution. Population differentiation is not consistently higher in parasite than in host. Therefore we reject the magnifying glass hypothesis.